Ivy leaves extract EA 575 in the treatment of cough during acute respiratory tract infections: meta-analysis of double-blind, randomized, placebo-controlled trials - Andreas Völp; Jennifer Schmitz; Michael Bulitta; Esther Raskopf; Cengizhan Acikel; Ralph Mösges (Scientific Reports, 2022)
Abstract Ivy leaves extracts have been used successfully to treat acute cough, and data from well-controlled trials is accumulating. We present a meta-analysis of two double-blind, randomized, placebo-controlled trials. Patients with acute respiratory tract infection (ARTI) received ivy leaves dry extract EA 575 (n = 228) or placebo (n = 162) for 7 days, followed by a 7-day period without treatment. The main efficacy outcome was the Bronchitis Severity Score (BSS). Individual patient data meta-analyses were performed using mixed models for repeated measures, analysis of covariance and logistic ordinal regression. Significant BSS differences between EA 575 and placebo occurred already after 2 days and increased until treatment end, with BSS reductions of 8.6 ± 0.2 and 6.2 ± 0.2 (marginal means ± SEM; p < 0.001). The score reduction for placebo after 7 days was comparable to that for EA 575 after 4 days. In the EA 575 group, the proportion of cough-free patients was 18.1% at treatment end and 56.2% at end of follow-up, compared to 9.3% and 25.6% for placebo, respectively. Adverse event rates for EA 575 and placebo were comparable. EA 575 reduces effectively the intensity of acute cough associated with ARTIs and leads to a significant acceleration of recovery. No safety signals were observed.